Supressão de acasalamentos e redução de danos de Spodoptera frugiperda (J. E. Smith, 1797) no algodoeiro - Schirmer, Fabiano G.; Favetti, Bruna M.; Clark, Thomas; Galvan, Tederson; Cordeiro, Erick M. G.; Vivan, Lucia; Tran, Khai; Broms, Kristin; Miranda, Ricardo (Entomological Communications, 2023)
The control of Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae) in cotton (Gossypium hirsutum L.) has been limited by the rapid development of resistance to insecticides and Bt toxins. The fall armyworm has become increasingly present in cotton fields, becoming a major problem for growers. Therefore, the demand for new and more sustainable tools for managing this pest has increased in recent years. Ideally, the new tool should be compatible with other available control tactics, such as the use of Bt plants, and it should be implemented following IPM principles. In this study, we tested the efficacy of a liquid pheromone formulation for the Fall armyworm control in Bt and conventional cotton varieties in the Brazilian Midwest. Our results showed that the capture of insects in traps has been reduced by 85% in areas treated with pheromone compared to control suggesting high levels of mating suppression. Pheromone treatment also resulted in 70% less damage to cotton reproductive structures when compared to areas not treated with the pheromone in conventional cotton. Moreover, applying pheromone provided an additional benefit to Bt cotton, resulting in 85% damage reduction. Our results show the effectiveness and feasibility of mating disruption with pheromone as an important management tactic for Lepidopterans in cotton. However, no significant differences were found in yield in the conditions tested. These results represent a potential key step toward developing more sustainable tools for pest management in Brazil.